Physiological Basis of Salinity Tolerance in Foxtail Millet (Bangladesh Agronomy Journal, 2020)
A pot experiment was conducted to study the effects of salt stress on physiological parameters associated to salinity tolerance in foxtail millet plant in the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during March to May, 2018. Four foxtail millet genotypes namely i) BD-881 ii) BD-897 iii) BD-878 and iv) BARI kaon-1 were grown and each pot was irrigated using three levels of saline water viz. control (tap water), 60 mM saline water and 120 mM saline water. Results indicated that genotypic variability was profound in salinity tolerance in foxtail millet. The leaves of BD-878 maintained higher water content, higher accumulation of proline, and lower accumulation of malondialdehyde (MDA) as well as less reduction of chlorophyll compared to other genotypes studied. BD-878 also showed relatively higher salinity stress tolerance, while BD-897 was susceptible in relation to yield. Higher salinity tolerance in BD-878 was associated with higher relative leaf water and chlorophylls with accumulation of higher amount of proline and lower accumulation of malondialdehyde content.Bangladesh Agron. J. 2019, 22(2): 11-24